Análisis temporal de la población reclusa española: Las leyes de Quételet - Ruiz Morales, Manuel L. (Archivos de criminología, seguridad privada y criminalística, 2020)
This article will study the spanish prison population, which will be considered like a statistical sequence –as time series analysis-, in order to examine questions of statistical trend and the seasonality, because they have influenced to the prison population in Spain. Thus, the objective is to observe the possible variation of the prisoners number´s in the spanish jails´s, according to the time of year. Thereby, the results obtained can be explained (at least partially) by “thermics laws” theory of Adolphe Quetelet.